A familial syndrome of hypocalcemia with hypercalciuria due to mutations in the calcium-sensing receptor. - Pearce, S; Williamson, C; Kifor, O; Bai, M; Coulthard, MG; Davies, M; Lewis-Barned, N; McCredie, D; Powell, H; Kendall-Taylor, P; Brown, E; Thakker, R (1996)
BACKGROUND: The calcium-sensing receptor regulates the secretion of parathyroid hormone in response to changes in extracellular calcium concentrations, and mutations that result in a loss of function of the receptor are associated with familial hypocalciuric hypercalcemia. Mutations involving a gain of function have been associated with hypocalcemia in two kindreds. We examined the possibility that the latter type of mutation may result in a phenotype of familial hypocalcemia with hypercalciuria. METHODS: We studied six kindreds given a diagnosis of autosomal dominant hypoparathyroidism on the basis of their hypocalcemia and normal serum parathyroid hormone concentrations, a combination that suggested a defect of the calcium-sensing receptor. The hypocalcemia was associated with hypercalciuria, and treatment with vitamin D resulted in increased hypercalciuria, nephrocalcinosis, and renal impairment. Mutations in the calcium-sensing-receptor gene were identified by DNA-sequence analysis and expressed in human embryonic kidney cells (HEK-293). RESULTS: Five heterozygous missense mutations (Asn118Lys, Phe128Leu, Thr151Met, Glu191Lys, and Phe612Ser) were detected in the extracellular domain of the calcium-sensing-receptor gene and shown to cosegregate with the disease. Analysis of the functional expression of three of the mutant receptors in HEK-293 cells demonstrated shifts in the dose-response curves so that the extracellular calcium concentrations needed to produce half-maximal increases in total inositol phosphate in the cells were significantly (P=0.02 to P<0.001) lower than those required for the wild-type receptor. CONCLUSIONS: Gain-of-function mutations in the calcium-sensing receptor are associated with a familial syndrome of hypocalcemia with hypercalciuria that needs to be distinguished from hypoparathyroidism.